Comparison of targeted next-generation sequencing and Sanger sequencing for the detection of PIK3CA mutations in breast cancer. Issue 1 (December 2015) - Arsenic, Ruza; Treue, Denise; Lehmann, Annika; Hummel, Michael; Dietel, Manfred; Denkert, Carsten; Budczies, Jan
Abstract Background Phosphatidylinositol-4, 5-bisphosphate 3-kinase, catalytic subunit alpha, PIK3CA, is one of the most frequently mutated genes in breast cancer, and the mutation status ofPIK3CA has clinical relevance related to response to therapy. The aim of our study was to investigate the mutation status of PIK3CA gene and to evaluate the concordance between NGS and SGS for the most important hotspot regions in exon 9 and 20, to investigate additional hotspots outside of these exons using NGS, and to correlate thePIK3CA mutation status with the clinicopathological characteristics of the cohort. Methods In the current study, next-generation sequencing (NGS) and Sanger Sequencing (SGS) was used for the mutational analysis ofPIK3CA in 186 breast carcinomas. Results Altogether, 64 tumors hadPIK3CA mutations, 55 of these mutations occurred in exons 9 and 20. Out of these 55 mutations, 52 could also be detected by Sanger sequencing resulting in a concordance of 98.4 % between the two sequencing methods. The three mutations missed by SGS had low variant frequencies below 10 %. Additionally, 4.8 % of the tumors had mutations in exons 1, 4, 7, and 13 ofPIK3CA that were not detected by SGS.PIK3CA mutation status was significantly associated with hormone receptor-positivity, HER2-negativity, tumor grade, and lymph node involvement. However, there was no statistically significant association between thePIK3CA mutation status and overall survival. Conclusions Based on our study, NGS is recommended as follows: 1) for correctly assessing the mutation status ofPIK3CA in breast cancer, especially for cases with low tumor content, 2) for the detection of subclonal mutations, and 3) for simultaneous mutation detection in multiple exons.